(untitled) (The Pakistan Development Review, 2011)
This study empirically examines the role of economic freedom, market size and exchange rates in attracting foreign direct investment in south Asian countries for the period 1995-2008 by employing panel data analysis in fixed effect setting. Results clearly indicate the presence of significant positive relationship between economic freedom and FDI inflows in South Asian countries during the period of study. The real effective exchange rate was having negative association with it indicating that depreciation in host country currency negatively influences the inflow of FDI to that country. Therefore, monetary policy should focus on providing stability to currencies of host countries. The model explains approximately 90 percent of total variation in FDI. The paper concludes that South Asian countries should make concerted efforts in devising polices that improve level of economic freedom. In other words, they should provide more investment friendly climate, trade openness, efficient monetary and fiscal policies and freedom from corruption. This can help to attract more foreign direct investment in the South Asian countries.